Story-“Record” vs Spontaneous Narrative in Light of a Comparative Analysis of Linguistic Feature - E. E. Burova; A. A. Racheva; U. E. Chekmez (Научный диалог)
A memoir-type narrative as a structured text in a certain way, represented by at least two types of oral story: (1) a repeatedly reproduced narrative (a story about the war) and (2) an unprepared segment of a speech (a story about life in Irkutsk during the existence of the USSR and after its collapse) is considered in the article. The first variety in the scientific literature was called the “record” story. In the course of comparing the two fragments related to the mentioned types of narration, the phonetic, lexical and grammatical means used by the subject of speech and reflecting the specifics of the story-“record” on the theme of war are characterized. Thanks to an integrated approach to the linguistic features of the narrative, detailed conclusions are drawn regarding its organization. It has been established that at different linguistic levels the story-“record” has certain distinctive features, the most important of which are the use of functionally loaded prosodic means and the almost complete absence of speech failures, the use of a large number of bookish lexical elements, as well as grammatical structures characteristic of the official business language, written speeches. It is proved that all the identified features allow the speaker to give the features of a collectively significant memory to personal impressions of the war.